PREVENTION OF ACUTE EROSIVE AND ULCERATIVE LESIONS OF THE UPPER GASTROINTESTINAL TRACT IN PATIENTS WITH EXTENSIVE THERMAL BURNS - Abidov Utkir (Web of Journals Publishing, 2024)
The article explores the prevention of acute erosive and ulcerative lesions in the upper gastrointestinal tract of patients suffering from extensive thermal burns. It discusses the high incidence of these complications, often leading to severe outcomes like bleeding and multiple organ failure. Through endoscopic research, the early development of ulcers post-burn is detailed, along with their treatment using conservative methods primarily, including the use of proton pump inhibitors like omeprazole. The study also highlights the importance of understanding the pathogenesis of these ulcers, emphasizing the role of increased acid production and delayed gastric motility in their development.
Keywords: Acute erosive and ulcerative lesions, Upper gastrointestinal tract, Thermal burns, Hemodynamic disorders, Gastric motility, Proton pump inhibitors.